THE LEVEL OF WELFARE OF FISHERMAN IN THE JOINT CAPTURE FISHERIES BUSINESS GROUP IN HANDIL TERUSAN VILLAGE, ANGGANA DISTRICT KUTAI KARTANEGARA REGENCY - Oktawati, Nurul Ovia (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2022)
This research aim was to analze prosperity level based on indicator of Fisherman Exchange Value (Nilai Tukar Nelayan/NTN) and Index of Fisherman Exchange Value (Indeks Nilai Tukar Nelayan/INTN) community business group with capture Fisheries in Handil Terusan Village. This research was conducted on May 2021 to June 2022 in the Handil Terusan Village, Anggana Sub-District, Kutai Kartanegara Regency. Research was used the case study method and applied purposive sampling to select 25 respondents of 5 fishing groups. Data were analyzed by qualitative-quantitative descriptive method that focused on Fisherman Exchange Value (Nilai Tukar Nelayan/NTN) and Index of Fisherman ExchangeÂ Value (Indeks Nilai Tukar Nelayan/INTN). The results of the NTN analysis show that in general the NTN value for fishing families from 5 joint capture fisheries business groups in 2020 and 2021 is above 1 and has increased. The results of the INTN analysis of fishing families in 2020 and 2021 show that 3 groups of Fishermen have increased and 2 groups of Fishermen have decreased.Â Key WordsÂ : Fisherman Exchange Value (NTN), Handil Terusan Village, Index of Fisherman Exchange Value /INTN, Prosperity